Analisis Resiko Gempa Bendungan Leuwikeris, Provinsi Jawa Barat [Seismic Hazard Analysis Leuwikeris Dam, West Java] - Ariyandi, Fioliza; Harahap, Muhammad Riza (Universitas Pelita Harapan, 2018)
One of the dams in West Java is Leuwikeris Dam is being planned. It required an assessment in the form of seismic hazard analysis on Leuwikeris Dam. In this paper seismic hazard analysis was performed using probabilistic and deterministic methods. Where seismic events in the repeat periods of 145, 475 and 10000 years are considered in seismic hazard analysis by probabilistic methods. While the spectra target selection is based on CMS (Conditional Mean Spectrum). The results of this study show the design criteria for seismic risk Leuwikeris Dam on condition Operating Basis Earthquake (OBE) and Safety Evaluation Earthquake (SEE) in the form of acceleration time history. In short spectra t = 0.2 seconds value peak ground accelerations (PGA), respectively for 0,23g, 0,30g and 0,54g, while in the long spectra period t = 1.0 seconds value of peak ground accelerations (PGA) respectively of 0.16g, 0.19g and 0.26g, which will be used as input in conducting a dynamic analysis of Leuwikeris Dam.